E-WOM, influencers, and online reviews in Wardah cosmetics purchase decisions on Shopee - Tengku Syarifah; Dian Wahyuni; Tri Andriani; Putri Sandini (Priviet Social Sciences Journal, 2025)
This study aims to determine the Influence of E-WOM, Influencers, and Online Customer Reviews on Purchasing Decisions. The population in this study was Shopee platform users in the Kisaran City area, the number of which cannot be known for certain. This study used the Wibisono formula. The data used were primary data, and this study was conducted online using an electronic questionnaire, namely Google form. The data analysis tool used multiple linear regression. The results of the study show the Influence of E-WOM, Influencers, and Online Customer Reviews on Purchasing Decisions. Simultaneously, E-WOM (X1), Influencer (X2), and Online Customer Review (X3) influence Purchasing Decision (Y), Fcount > Ftable (44.226 > 2.70) with a significance of 0.000 < 0.05. This shows that the research results H1 were accepted and H0 was rejected. While partially E-WOM (X1) has a positive and significant effect on Purchasing Decisions (Y), with a calculated t value > ttable, namely 3.693 > 1.98580 with a sig t value for the E-WOM variable (X1) 0.000 smaller than α 0.05, namely 0.000 < 0.05, Influencer (X2) has a positive and significant effect on Purchasing Decisions (Y), with a calculated t value > t-table, namely 3.693 > 1.98580 with a sig t value for the Influencer variable (X2) 0.000 smaller than α 0.05, namely 0.000 < 0.05 and Influencer (X2) has a positive and significant effect on Purchasing Decisions (Y), with a calculated t value > ttable, namely 2.067 > 1.98580 with a sig t value for the Influencer variable (X2) 0.042 is smaller than α 0.05, which is 0.042 <0.05, it can be concluded that H0 is rejected, H2 is accepted and the R Square coefficient is 0.577 or 57.7%. This shows that the Purchase Decision (Y) can be explained by the E-WOM variable (X1), influencer (X2), and Online Customer Review (X3), amounting to 457.7%, and the remaining 42.3% is explained by other factors not examined in this study.